Effect on body weight and composition in overweight/obese Australian adults over 12 months consumption of two different types of fibre supplementation in a randomized trial. Issue 1 (December 2016) - Pal, Sebely; Ho, Suleen; Gahler, Roland; Wood, Simon
Abstract Background/Objectives Higher fibre intakes are associated with risk reduction for chronic diseases. However, many people find difficulty in consuming sufficient fibre through their diet. Supplements may be an effective alternative. We aimed to investigate the effects of PolyGlycopleX® (PGX®), a proprietary polysaccharide complex and a proprietary Psyllium product (PgxSyl™) (PSY) on diet, body weight and composition in overweight and obese individuals. Subjects/Methods This was a double-blind 52 weeks study with 159 people randomized to 3 groups: control (rice flour); PGX (PGX) and proprietary psyllium (PSY). Participants did not change any of their usual habits or diet except they consumed 5 g of supplement taken with a total of 500 ml of water 5–10 min before meals. Results Weight was significantly lower in the PGX group compared to control at 3 (−1.6 kg [0.57, 2.67, p  = 0.003]), 6 (−2.6 kg [1.01, 4.13, p  = 0.001]) and 12 months (−2.6 kg [0.59, 4.64, p  = 0.012]) and in the PSY group compared to control group at 3 (−1.1 kg [0.07, 2.12, p  = 0.037]) and 6 months (−2.4 kg [0.95, 3.93, p  = 0.002]). This was a difference of − 2.8% for the PGX group and − 1.5% for the PSY group compared to control after 12 months supplementation. Body Fat was significantly lower in PGX compared to control at 6 (−1.8 kg [0.63, 2.95, p  = 0.003]) and 12 months (−1.9 kg [0.43, 3.36, p  = 0.012]) and in PSY compared to control at 6 (−1.9 kg [0.84, 3.04, p  = 0.001]) and 12 months (−1.4 kg [0.08, 2.71, p  = 0.038]). Conclusions PGX was better than PSY at maintaining dietary changes and weight loss over the 12 month intervention period, with no change to exercise. A simple strategy of PGX supplementation may offer an effective solution to long-term weight-loss and then management without the need for other nutrient modification. Trial registration ANZCTR:ACTRN12611000415909 . Registered 20 April 2011